Caracterización de Procesos y Diseño de Distribución en Planta de la empresa Leal Daccarett S.A.S. (2023)
The document presents a proposal for plant distribution in the company Leal Daccarett S.A.S, dedicated to the design of haute couture garments, showing the relevance in the study related to times and movements to minimize delays in the production process. The proposal begins with the Characterization of Processes and Plant Distribution Design, analyzing the current situation regarding the production process, plant distribution, machinery and equipment used in production, movement and handling of materials, personnel, work periods and environmental situations; Once the findings have been found, a proposal for the implementation of the new plant distribution is designed in order to optimize processes, minimize times and improve the timely delivery of the finished product, in the specific case the party dress, designed under the best quality standards and at the same time a competitive product in national and international fashion markets.